Health Behaviors and Clinical Outcomes Among Patients with Myocardial Infarction in Indonesia - Herliani, Yusshy Kurnia; Matchim, Yaowarat; Kritpracha, Charuwan (Universitas Airlangga, 2015)
Introduction: Health behaviors are necessary for preventing possible cardiac events and maintaining health for MI patients. In addition to health behaviors, measuring clinical outcomes is a critical element for optimizing treatment and monitoring the risk factors of a cardiac event. The aims of this study were to (1) describe health behaviors and clinical outcomes among patients with myocardial infarction (MI) in Indonesia; and (2) investigate the relationship between their health behaviors, clinical outcomes, and other selected variables. Method: Sixty hospitalized MI patients participated in this descriptive correlational study. Data were analyzed using descriptive and correlational statistics. Results: The majority of MI patients in this study had a moderate level of total health behaviors, exercise behaviors, dietary behaviors, and stress management. Interestingly, most of the patients had a high level of medication adherence, and smoking cessation. Also, their blood pressure (BP) and body mass index (BMI) of MI patients were at the normal level. In contrast, more than half the patients had a high level of fasting blood glucose and total cholesterol, and a low level of HDL. Moreover, nearly half of the patients presented a high level of LDL, and triglyceride. Exercise behaviors have a negative relationship with total cholesterol, and LDL. Interestingly, gender showed a positive relationship with total health behaviors, and smoking cessation. In addition, monthly incomes show a positive relationship with exercise behavior, and dietary behaviors. The number of times hospitalized appeared to have a positive relationship with systolic BP. Surprisingly, MI treatments showed a positive relationship with total health behaviors, smoking cessation, and BP. Discussion: In conclusion, cardiac rehabilitation should involve health behaviors and clinical outcomes to prevent recurrent cardiac events and maintain health for MI patients.Keywords: Myocardial infarction, Health behaviors, Clinical outcomes